A comparative study on biopharmaceutical function of curcumin and miR-34a by multistimuli-responsive nanoniosome carrier: In-vitro and in-vivo - Abtahi, Najmeh Alsadat; Naghib, Seyed Morteza; Haghiralsadat, Fateme; Akbari Edgahi, Mohammadmahdi; Askari, Esfandyar (Frontiers in Molecular Biosciences, 2022)
This research conducted a comparative study on nanoscaled niosomal structures consisting of cationic surfactants: Tween-80, Tween-60, Cholesterol, and dioleoyl-3-trimethylammonium propane (DOTAP). Thin-film hydration is used to prepare curcumin and gene-entrapped noisome for enhancing stability and delivery rate. The influence of Tween 80, Tween 60, cholesterol, and DOTAP on the entrapment efficiency (EE) of curcumin and physicochemical properties of the carrier are fully discussed. The engineered formulation resulted in a positive charge of +11.23 mV, a high EE (100%), smooth-surface shape, spherical form, small diameter (90 nm), good stability in physiological buffers. and accelerated cellular uptake, as well as drug release of 32.1 31.98 % in PBS (pH 7.4 and 37°C) after 72 hours. Additionally, the cytotoxic activity of curcumin (Cur)/miR-34a-loaded nanoparticles is determined by the MTT assay. The result displayed the improved cytotoxic activity of Cur-niosome towards cancer cells compared to free-dispersed Cur. After administration of Cur in nano-noisome compared to Cur freely presented in cancer cell lines (A280s and A280cp-1), Cur concentrations dropped 2.5 folds, respectively. Generally, Cur-noisome exhibits a significant accumulation of superior anti-cancer properties. Likewise, the cytotoxicity of miR-34a-niosome against tumor cells was higher in comparison with the free gene. The anti-cancer effects of the gene/drug delivery were investigated in the 4T1 xenografted Balb/C mouse tumor model. According to the in-vitro and in-vivo results, gene delivery from the modified niosome nanoparticles was distinctly greater than Cur delivery, solely. Therefore, nano-niosomal gene therapy is a promising procedure for cancer treatment.